System spectral analysis of the fractal ultra-wideband signals - Chernogor, L.F.; Kravchenko, S.G.; Lazorenko, O.V. (Вопросы атомной науки и техники, 2015)
The theoretical basis and practical peculiarities of the system spectral analysis are briefly considered. The necessity and the expediency of simultaneously application of different linear and non-linear integral transforms during the system spectral analysis performance are explained. The system spectral analysis usage for investigations of the time-frequency structure of the fractal ultra-wideband signals is shown to be effective and useful.